Synthesis, anti-tuberculosis activity and QSAR study of 2,4-diarylquinolines and analogous polycyclic derivatives - Muscia, Gisela Celeste (2019)
The multicomponent syntheses of 2,4-di-aryl-quinolines and analogous polycyclic derivatives as anti-tuberculosis agents were described. They were prepared via Beyer and Friedländer methods under microwave irradiation in short reaction times and good yields. Several homogeneous and heterogeneous acid catalysts were compared for preparing 2,4-di-arylquinolines and among them trifluoroacetic acid (TFA) reached the higher yields. Two derivatives exhibited activity against Mycobacterium tuberculosis H37Rv (Mtb), underwent additional testing and were considered lead compounds. The synthesis of a series of polycyclic analogous led to six new active compounds and a Quantitative Structure Activity Relationship study (QSAR) study was established.